Recurrent giant cellulitis-like sweet syndrome induced by SARS-CoV-2 Pfizer-BioNTech mRNA vaccine - Penelope Hirt; Lily Park; Carly E. Wallace; Francisco Kerdel (PAGEPress Publications, 2023)
Primary and booster vaccines for COVID-19 are the most effective method of preventing infection and are generally considered safe. However, many cutaneous adverse events have been reported following vaccination. To date there have been seven reported cases of Sweet syndrome occurring following the first dose of the SARS-CoV-2 vaccine. We describe a rare case of atypical giant-cellulitis like Sweet syndrome reemerging after receiving the SARS-CoV-2 booster vaccine.